Perfil del visitante y las actividades de aventura en la Cascada Pailón de San Jacinto en la Parroquia Febres Cordero, cantón Babahoyo, Provincia de Los Ríos - Freire Arboleda, Zoila María (2019)
This research is directed to the study of the visitor profile and development of adventure activities in the Pailón San Jacinto Waterfall, through this work it was possible to show several factors that prevent the development of the natural tourist activity little known by the community in reference to the scarce implementation of adventure activities, access to tourist attractions, poor tourist signage on the trails. Taking into account the methodology that was applied as interviews and surveys for the development of this research, pertinent recommendations were made to contribute to the increase in tourism activity in the sector such as: implementing a tourist information point, tourist signage on the trails, the complementary services they would like to find during the trip, and adventure activities